PERSEPSI TENTANG UU CIPTA KERJA SERTA DAMPAKNYA TERHADAP MOTIVASI KERJA KARYAWAN - Erika, Fransiska; Rifa’i, Muhamad; Agustim, Warter; Suci Sayekti, Rr. Nugraheni Suci Sayekti (Unitri Press, 2024)
The purpose of this study is to determine the influence of employee perception on the job creation law regarding the certainty of employee rights, job opening, employee comfort and security, and to help employees affected by layoffs to work motivation both partially and simultaneously. The method used was the quantitative method, the data used was secondary data and primary data obtained from the distribution of questionnaires to be filled out by 92 respondents, data analysis was using multiple linear regression analysis, hypothesis testing using t-test and f-test. The results of the study showed that the certainty of employee rights, job opening, employee comfort, and helping employees affected by layoffs had a significant effect on work motivation in the network in Taman Rekerasi Sengkaling, both partially and simultaneously.